Pentanahan untuk Perlindungan Peralatan dan Bangunan Gedung - Agus Sugiharto (Swara Patra, 2019)
One of the causes of fire or damage to electrical equipment, installations and buildings is caused by a fault in the grounding system caused by a surge in electricity such as lightning and electrical fault such as short circuit currents and overloads. For this reason, a good grounding system plan is needed so that the disruption of electricity fault can be minimized. The effectiveness of the system of a protective device against lightning strikes and electrical fault will depend on grounding and bonding which if not done properly will result in system failure and can result in damage to electrical equipment and other buildings.